Analysis of proviral load levels in HTLV-1 carriers with different neurological impairment conditions (Research, Society and Development, 2021)
Objectives: To analyze the levels of proviral load (CPV) in patients with HTLV-1 with different conditions of neurological impairment. Methodology: Cross-sectional study, conducted from March to October 2017, with 43 patients with HTLV-1, divided into three groups in decreasing order of neurological involvement, according to the updated proposal of the clinical diagnosis criteria for HAM / TSP: Defined for HAM / TSP (Group 1, n = 7); Probable / Possible for HAM / TSP (Group 2, n = 9); Without HAM / TSP (Group 3, n = 27). The ANOVA test (one criterion) was used to verify the difference between the groups' mean CPV (p-value≤0.05). Results: The groups presented the following average CPV values: G1 = 9.00 ± 11.18; G2 = 1.88 ± 3.92; G3 = 2.81 ± 4.03 copies / 106 PBMC. In the intergroup comparison, of the difference between the means of CPV, a significant difference was observed between groups 1 and 2 and between groups 1 and 3 (p